(untitled) (Shahroud Journal of Medical Sciences, 2019)
Background: Diagnosis of separation anxiety disorder (SAD) in childhood is a critical risk factor of mental health in adulthood. Etiology studies have indicated the significant role of parental psychological factors in children with SAD phenomena. The purpose of present study was to investigate the effectiveness of parental reflective functioning -based psycho-educational program on improvement of children with separation anxiety disorder. Methods: A single-case experimental design with multiple baselines has been utilized to conduct present study. Subjects of the study included 4 parents (two mothers and two fathers) with children suffering from separation anxiety disorder who referred to psychiatric counseling center and clinic of child and adolescent psychiatrist in Mashhad during May and June of 2010. These parents were selected through convenience purposeful sampling method based on inclusion and exclusion criteria and participated in 12 sessions (two sessions per week) of a parental reflective functioning-based psycho-educational program. The participants completed the parent-separation anxiety questionnaire in three stages of baseline during the implementation of the program (in sessions 5, 9 and 12) as well as one month after follow-up. The obtained data were analyzed using indicators of Percentage recovery / PR, Effect size and Reliable Change Index (RCI). Results: At the end of the psycho-educational program, the results indicated a significant clinical decrease in the severity of separation anxiety in all four parents. at the end of psycho-educational program, the total score of recovery percentage for the first, second, third and fourth subjects was equal to 70.86, 71.30, 72.21 and 70.96, respectively. The RCI indicator of subjects was -9.93, -10.97, -11.59 and -11.26, respectively. Also, the effect size for the first, second, third and fourth subjects were equal to 7.43, 8.21, 8.67 and 8.43, respectively. Moreover, the overall improvement of all four subjects in subscales of fear of being left alone, fear of abandonment, fear of physical illness and fear of dangerous events was 66.75%, 71.10%, 70.39% and 71.73%, respectively which the values were significant in the clinical term. This improvement process continued throughout the follow-up period. Conclusions: according to research findings, the parental reflective functioning-based psycho-educational program has a positive effect on improving the symptoms of separation anxiety disorder in children. Therefore, it is recommended to utilize from this program in treatment interventions for separation anxiety disorder. Keywords: separation Anxiety Disorder, Psycho-Educational Program, Parental Reflective Functioning.